The Effect of Corporate Governance, Profitability, and Capital Structure on Corporate Risk Disclosure, with Company Size as Moderation - Hernawati Hernawati; Herman Ruslim (Green Publisher Indonesia, 2024)
One of the information factors needed by investors is the disclosure of company risk. with the disclosure of risk, information users can find out the condition of the company and whether the company's risk can affect the funds they invest, this study aims to examine the effect of corporate governance, profitability, and capital structure on company risk, this study also uses banking company data obtained from the Indonesian stock exchange for the period 2018 to 2022, and the research method ii is quantitative research. The sample selection technique used was purposive sampling and obtained 45 bank companies so that the total amount of observation data was 225 data. The data analysis method in this study is multiple linear regression using panel data regression with a fixed effect model.